Koulutuksen ja lapsi-vanhempisuhteen yhteys elämässä selviytymiseen sosiaalinen perimä ja koulutuskultuurisen pääoman periytyminen sukupolvesta toiseen - Kärkkäinen, Tuulikki (Research report / Department of Teacher Education, University of Helsinki, 2004)
Abstract: The relation of education and child-parent relationship with coping with life : social and educational culture capital heritage from one generation to the next.